“E comé que a gente sobrevive? A gente segura a mão uma das outras”: o assédio sexual na pós-graduação em administração numa perspectiva afrocêntrica - Santos, Luana Sodré da Silva (2023)
Black women in academic settings, particularly in teaching and research roles, face obstacles that impact their entry and persistence as knowledge producers and education professionals. Among these challenges, sexual harassment stands out as a patriarchal gender violence that violates the victims integrity by undermining the autonomy of women as individuals. Treated as beings without subjectivities, their bodies are reduced to sexual objects, subjected to subjugation and violence by men. Specifically, Black women grapple with racial issues, emphasizing the need to broaden the concept of sexual harassment (SH). Beyond the legal context, a sociological discussion is undertaken, drawing on the concepts of cosmo-perception and worldview from Afrocentric theories to prioritize alternative perspectives and consider Black women as a collective subject. Additionally, African and Afro-diasporic authors are employed to reclaim the autonomy and humanity of Black women in postgraduate studies, exploring non-Eurocentric ways of being and living. In predominantly white and male academia, literature indicates that these women are challenged for constructing knowledge that goes against the hegemonic narrative. Instances of racism and sexism are found to hinder, marginalize, and discredit them. The methodological approach of “falavivência”; based on Conceição Evaristo’s concept of “Escrevivência” is used to orally explore how they experience their academic journeys in the field of Administration. Conversations with academic leaders in the field of Administration are also conducted to understand institutional responses to sexual harassment in their spaces. Falavivências reveal the adversities of existing in unwelcoming spaces. Notably, among the reported violences are epistemicides, silencings, sexual harassment based on gender, and associations with stereotypes like mulatto, black mother, and domestic worker. These incidents, whether interconnected or isolated, aim to position them in the realm of non-being, causing both visible and invisible wounds. Conversely, survival strategies rooted in collectivity are observed, enabling them to persist and claim their rightful space. The concept of “quilombo” emerges as a path to reclaim self-knowledge and self-definition. In this thesis, falavivência fosters affectionate connections with participants, including the researcher. The care, affection, and metaphorical “lap” subvert the violent expectations imposed on them, facilitating the construction of another Black woman in control of her body, desires, and aspirations. Ultimately, by expanding the concept of sexual harassment, the thesis effectively addresses the violences they endure. The integration with Afrocentricity opens up new possibilities for being an woman “amefricana”.